Numerical analysis of phase change material for energy storage system / Wan Khairul Muzammil Abdul Rahim - Wan Khairul Muzammil, Abdul Rahim (2012)
A numerical method based on the effective heat capacity method was studied to solve the phase change heat transfer problems of a phase change material in a cylindrical latent heat thermal energy storage device during the charging (melting) process of the material. The commercial software COMSOL Multiphysics was employed to run the numerical simulations. The effective heat capacity method was used to characterize the fusion heat of melting of the phase change material and the moving boundary of solid-liquid interface. An analytical tool was used to validate the phase change heat transfer process in which the results show a good agreement between the numerical and analytical analysis. Subsequently, the effects of fins and various heat transfer velocities on the thermal behavior of the PCM were studied numerically using the software. Generally, the results obtained from the analysis show that the heat transfer rate increases as the number of fins and HTF velocities were increased. For small number of fins configurations, the effect of increasing the HTF velocities are not so significant, as the thermal resistance of the phase change material is high. However, the effect is more evident as the number of fins increases; due to the decreasing thermal resistance on the PCM side.